Contaminants of Emerging Concern as novel groundwater tracers for delineating wastewater impacts in urban and peri-urban areas. (1st December 2018) - McCance, W.; Jones, O.A.H.; Edwards, M.; Surapaneni, A.; Chadalavada, S.; Currell, M.
Abstract: Management and treatment of environmental impacts from wastewater treatment plants (WWTPs) is a major, worldwide, sustainability challenge. One issue associated with WWTP operation is the potential for groundwater contamination via leaking or infiltration of wastewater, particularly with inorganic nutrients (ammonia and nitrate) as well as persistent organic compounds. Despite the potential for such contamination to create environmental and health risks, conventional methods, such as the assessment of major ions, nutrients, bacteriological indicators and conventional tracers (such as stable and radiogenic isotopes) are often unable to provide accurate delineation of multiple potential sources of contamination. This is particularly important for WWTPs which often occur in urban, peri-urban or intensively farmed agricultural areas where multiple potential sources (such as livestock, fertilisers, wastewater irrigation, and domestic septic systems) may contribute similar contaminants. This review explores the applicability of promising novel groundwater tracers, such as Contaminants of Emerging Concern (CECs) and isotopic tracers, which can be used in conjunction with conventional tracers (i.e. 'co-tracers') to provide a more definitive assessment of contaminant sources, plume delineation and even (potentially) indicating the age of contamination (e.g., recent vs. legacy). The suitability of the novel groundwater tracers is evaluated according to four key criteria: (i). sufficient presence in raw wastewater and/or treated effluents; (ii) diagnostic of WWTP impacts as opposed to other potential off-site contamination sources; (iii) persistence in the subsurface environment; and (iv) amenable to rapid and sensitive analysis. Further analysis of various classes of CECs along with improved detection limits associated with improvements in analytical methodologies should allow for future application of promising groundwater tracers, providing WWTP operators and regulatory authorities a more definitive toolbox with which to assess groundwater contamination associated with site operations. These include: persistent pharmaceuticals and personal care products (carbamazepine, crotamiton, primidone, atenolol and sulfamethoxazole), artificial sweeteners (acesulfame, sucralose, saccharin and cyclamate) and potentially, certain pesticides (atrazine and simazine). Graphical abstract: Highlights: Identification of promising novel groundwater tracers and co-tracers. Improved delineation of wastewater impacts in urban and peri-urban areas. Contaminants of emerging concern (CECs) may be used with conventional markers. Separation of legacy vs recent contamination possible in certain cases. Outlines the importance of further research into this area.